2022
DOI: 10.1177/11206721221134171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of higher-order aberrations in relation to the clinical outcome of an enhanced monofocal IOL

Abstract: Purpose To analyse higher-order aberrations of an enhanced monofocal aspheric intraocular lens (IOL) in relation to the clinical outcome compared to a monofocal aspheric IOL. Setting Department of Ophthalmology, Charité – Universitätsmedizin Berlin, Germany Design Prospective, monocentric, controlled, non-randomized, two-armed study Methods After phacoemulsification, a total of 30 patients (60 eyes) were bilaterally implanted with either TECNIS Eyhance IOL model ICB00 (Johnson & Johnson Surgical Vision, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Our scoping review also included three cases series that were not included in the previous ones, [17,37,44] but the results provided in these three references were in agreement with the conclusions reported by Wan et al [6]. This scoping review also included a comparison study for IsoPure [44] IOL in contrast to previous systematic reviews that only included Tecnis Eyhance.…”
Section: Strengths and Limitationssupporting
confidence: 76%
See 3 more Smart Citations
“…Our scoping review also included three cases series that were not included in the previous ones, [17,37,44] but the results provided in these three references were in agreement with the conclusions reported by Wan et al [6]. This scoping review also included a comparison study for IsoPure [44] IOL in contrast to previous systematic reviews that only included Tecnis Eyhance.…”
Section: Strengths and Limitationssupporting
confidence: 76%
“…Regarding the laboratory evidence, the elevation changes for refractive EDoF lenses were not achieved for Table 5 Criteria accomplished by the enhanced monofocals according to the ANSI standard definition of EDOF lenses and additional points RCT Randomized clinical trial, CS Case series ANSI-1: Statistical significance versus control for mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm ANSI-2: An increase in depth of field is achieved in the monocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR ANSI-3: The median monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR ANSI-4: Monocular acuity at distance, with correction at this distance, is statistically non-inferior to control using a non-inferiority margin of 0.1 logMAR Add-1: Statistical significance versus control for mean binocular visual acuity, with distance correction, at an intermediate distance of 66 cm Add-2: An increase in depth of field is achieved in the binocular defocus curve with distance correction equal to or greater than 0.5 D for a visual acuity level of 0.2 logMAR Add-3: The mean monocular visual acuity, with distance correction, at an intermediate distance of 66 cm, is at least 0.2 logMAR Add-4: Starting with CDVA, the monocular defocus range at 0.2 logMAR is ≥ 1.5 and < 2. Bova et al [44], Nanavaty et al [39], Corbelli et al [49], Lopes et al [40], Steinmüller et al [17], Auffarth et al [45], Ucar et al [37], Kang et al [41], Unsal et al [38], Cinar et al [42], Huh et al [28], Yangzes et al [36], Eguileor et al [43], Mencucci et al [3], Garzón et al [46] the Tecnis Eyhance [31,32], and the optical quality studies that included both, enhanced monofocals and EDoF lenses, showed a higher depth of focus range with poorer distance optical quality for EDoF lenses in comparison to enhanced monofocals [25,27]. These laboratory results were in agreement with clinical evidence of studies including enhanced monofocals and EDoF lenses, demonstrating a higher range of focus and better DCNVA for the latter [33][34][35]49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contrast sensitivity results aligned with those of monofocal lenses investigated by our research group. [11][12][13] Several independent studies consistently emphasize the exceptional contrast vision achieved with refractive segmental IOLs, conclusively establishing their equivalence with monofocal IOLs. [21] This remarkable consistency in contrast vision performance underscores the clinical value of refractive segmental IOLs in ensuring excellent post-operative vision quality.…”
Section: Discussionmentioning
confidence: 85%